Low temperature synthesis of novel rodlike Bi 5O 7I with visible light photocatalytic performance - Cao, J.; Li, Xin Yong; Lin, H.; Xu, B.; Luo, B.; Chen, S. (2012)
Novel rodlike Bi5O7I was successfully synthesized via precipitation transformation method using BiOI as a precursor at 70 °C. The scanning electron microscopy (SEM) and X-ray diffraction (XRD) results show that Bi5O7I had rodlike structure with good crystallinity and purity. The UV–vis diffuse reflectance spectroscopy (DRS) displays that the absorption band edge of Bi5O7I was 422 nm, which ensures the good visible light absorption of Bi5O7I. The application of photocatalytic degrading rhodamine B (RhB) under visible light (λ > 400 nm) presents that the as-prepared rodlike Bi5O7I had excellent photocatalytic activity compared to single BiOI and TiO2 (P25). It is a promising visible light induced photocatalyst for the treatment of chemically polluted water.